THE EFFECT OF AUTHENTIC LEARNING APPROACHES AND ASSESSMENT TECHNIQUES ON STUDENTS' STATISTICS BASIC TEST RESULTS BY INTELLIGENCE CONTROL - Isak Iskandar; Ahmad Ahmad (LPPM Universitas Negeri Jakarta, 2022)
The purpose of this study is to determine the effect of authentic learning approaches and assessment techniques on students' basic statistical learning outcomes by controlling intelligence. This research is a quasi-experimental research using a 2x2 factorial design which includes 80 samples of KPI students. The results are (1) the results of the basic statistical basic test of students who use a scientific approach are higher than students who use a contextual learning approach (2) the results of the basic statistical test of students who use essay tests are higher than students who use portfolio assessment (3) there are the effect of the interaction between the learning approach and authentic assessment techniques on the results of the basic statistical basic test of students (4) especially for students who learn to use essay assessment, the results of the basic statistical test of student groups with a scientific approach are higher than contextual learning (5) especially for students who learn to use portfolio assessment, the results of the basic statistical test of student groups with a contextual approach are lower than scientific learning (6) especially for students who learn to use a scientific approach, the results of the basic statistical test of student groups with essay assessments are more higher score than using portfolio assessment (7) especially for students who learn to use a contextual approach, the results of the basic statistical test for groups of students with portfolio assessment are lower than using essay assessment. Therefore, it is recommended for lecturers to know the success of students in receiving the material, it is better to use a scientific approach and form of essay assessment.